PENGARUH KARAKTERISTIK PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP KUALITAS IMPLEMENTASI CORPORATE GOVERNANCE (studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2013-2016) - Muhammad Donny Ramadhan; Mohammad Amin; Junaidi Junaidi (Universitas Islam Malang, 2017)
Abstrak The purpose of this research is to investigate the determinants of corporate governance implementation quality of Indonesian manufacture companies listed in BEI. This research uses 15 firm years for sample. Corporate governance implementation quality data are data for year 2013 until 2016. The variables that were hypothesized influence corporate governance implementation are ownership concentration, Growth, Leverage and SIZE using multiple regression method, this research found that ownership concentration and Leverage have positive influence to corporate governance implementation quality. Keywords: ownership concentration, growth opportunities, leverage, companies size and corporate governance implementation quality